The olfactory receptor gene repertoire in primates and mouse: Evidence for reduction of the functional fraction in primates - Rouquier, Sylvie (The National Academy of Sciences, 2000)
Olfactory receptors (ORs) located in the cell membrane of olfactory sensory neurons of the nasal epithelium are responsible for odor detection by binding specific odorant ligands. Primates are thought to have a reduced sense of smell (microsmatic) with respect to other mammals such as dogs or rodents. We have previously demonstrated that over 70% of the human OR genes have become nonfunctional pseudogenes, leading us to hypothesize that the reduced sense of smell could correlate with the loss of functional genes. To extend these results, we sampled the OR gene repertoire of 10 primate species, from prosimian lemur to human, in addition to mouse. About 221 previously unidentified primate sequences and 33 mouse sequences were analyzed. These sequences encode ORs distributed in seven families and 56 subfamilies. Analysis showed a high fraction (≈50% on average) of pseudogenes in hominoids. In contrast, only ≈27% of OR genes are pseudogenes in Old World monkeys, and New World monkeys are almost free of pseudogenes. The prosimian branch seems to have evolved differently from the other primates and has ≈37% pseudogene content. No pseudogenes were found in mouse. With the exception of New World monkeys, we demonstrate that primates have a high fraction of OR pseudogenes compared with mouse. We hypothesize that under relaxed selective constraints, primates would have progressively accumulated pseudogenes with the highest level seen in hominoids. The fraction of pseudogenes in the OR gene repertoire could parallel the evolution of the olfactory sensory function.